Revitalizar a cidade pelo planeamento da estrutura verde - Madureira, Helena (2013)
This paper identifies priority areas for intervention to promote the public green system in the municipality of Porto. The assessment and classification of the public green spaces allow us to define a Global Index of Proximity to Public Green System and to identify priority areas for intervention. Additionally, we present an example of green spaces connectivity enhancement by street tree plantings.